2018
DOI: 10.1016/j.omtn.2018.08.012
|View full text |Cite
|
Sign up to set email alerts
|

miR-7 Suppresses Tumor Progression by Directly Targeting MAP3K9 in Pancreatic Cancer

Abstract: Extensive research has suggested that miR-7 plays a critical role in cancer progression. However, the biological function of miR-7 in pancreatic cancer (PC) progression is poorly understood. Therefore, in the present study, we investigated the function of miR-7 and its molecular mechanism in PC progression. We used multiple methods, such as MTT, FACS, Transwell assay, RT-PCR, western blotting, and transfection to investigate the role of miR-7 in PC cells. We found that miR-7 suppressed cell growth, migration, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 36 publications
3
41
0
Order By: Relevance
“…Studies on miR-7 have been conducted in different types of tumors, and its function as a tumor suppressor has been demonstrated in pancreatic cancer (25) and glioma (26). In VSMCs derived from AAA in the present study, miR-7 suppressed proliferation and promoted the generation of ROS as well as LDH activity.…”
Section: Discussionsupporting
confidence: 48%
“…Studies on miR-7 have been conducted in different types of tumors, and its function as a tumor suppressor has been demonstrated in pancreatic cancer (25) and glioma (26). In VSMCs derived from AAA in the present study, miR-7 suppressed proliferation and promoted the generation of ROS as well as LDH activity.…”
Section: Discussionsupporting
confidence: 48%
“…miR-214 promoted radiosensitivity by inhibiting autophagy that was mediated by autophagy-related gene 12 (ATG12) in colorectal cancer ( 35 ). In recent years, several studies have demonstrated that miR-7 plays an antitumor role in tumorigenesis, including pancreatic ( 36 ), lung ( 7 ), thyroid ( 37 ), and gastric cancer ( 38 ). Concurrently, miR-7 has been revealed to reduce the levels of EGFR and AKT by activating the EGFR/PI3K/AKT signaling pathway, which delays radiation-induced DNA DSBs and increases the radiosensitivity of A549 cells, laryngeal squamous cell carcinoma SQ20B cells, breast cancer MDA-MB-468 cells and malignant glioma U251 and U87 cells ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, miR-7 has been reported to play an important role in regulating the biological process of various diseases [46,47]. For instance, miR-7 is a tumor suppressor and increase cisplatin sensitivity of gastric cancer cells by targeting mTOR, indicating its potential application for the treatment of human gastric cancer in the future [48].…”
Section: Discussionmentioning
confidence: 99%